Nutrição materna durante o terço final de gestação: reflexos sobre o desempenho na terminação e características pós-abate da progênie - Klein, John Lenon (2023)
The objective of the present work was to evaluate the effects of nutritional levels in the final third of gestation of beef cows on performance at finishing and post-slaughter characteristics of the progeny. Forty-one steers from cows submitted to different nutritional levels in the final third of pregnancy were used: 13 cows without supplementation on native pasture under nutritional restriction (RES); 16 cows supplemented to meet 100% energy and protein for maintenance (REQ); 12 cows supplemented to meet 150% energy and protein for maintenance (HIGH). The experimental design was completely randomized, with three treatments and different numbers of repetitions. Maternal nutrition during gestation did not affect daily dry matter intake (9.79 kg), however, HIGH steers tended to have longer daily feeding times (3.59 vs. 3.28 and 3.25 hours) and shorter idle (11.76 vs 12.41 and 12.15 hours) in relation to RES and REQ, respectively. Progeny performance was not influenced by maternal nutrition during gestation, with daily weight gain of 1.209 kg and average slaughter weight of 526.13 kg. However, REQ steers had a lower rate for Residual Feed Intake (CAR), while HIGH progeny had a higher rate for Residual Weight Gain (GPR). HIGH animals showed greater gain in body condition score (0.91 vs 0.54 points) and had lower concentration of the enzyme Aspartate transaminase (97.57 vs 112.43 U/L) in relation to RES. The other blood metabolites were similar between the RES, REQ and HIGH progenies (P>0.05). Among the post-slaughter measurements, REQ steers had a lower participation of the gastrointestinal tract (7.63 vs 8.22 and 8.28%) and rumen (2.24 vs 2.45 and 2.50%) in relation to body weight. empty. HIGH steers (11.41 points) tended to have lower carcass conformation than RES and REQ steers (12.00 and 12.68 points, respectively), but tended to have juicier meat in sensory analyzes (7.27 vs. 6.94 and 6.66 points, in the same order). The other sensory parameters, as well as the qualitative characteristics of the meat, were not influenced by maternal nutrition during gestation (P>0.05). Thus, the results obtained in the present study suggest that better maternal nutrition during final third of gestation produce more efficient (REQ) and more productive (HIGH) individuals in feedlot finishing systems. In addition, providing nutrients above the maternal requirement in the final third of gestation improves liver health and the quality of the meat product that reaches the consumer. On the other hand, maternal nutritional restriction during gestation leads to the formation of an “thrifty phenotype” in the RES offspring, an aspect that can lead to compensatory weight gain and suppress the effects of fetal programming in adult life.